2022
DOI: 10.1186/s10020-021-00427-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lipid droplets accumulation induced cognitive deficits in obstructive sleep apnea syndrome mice via JNK/SREBP/ACC pathway but not through PDP1/PDC pathway

Abstract: The mechanisms of chronic intermittent hypoxia (CIH)-induced cognitive deficits remain unclear. Here, our study found that about 3 months CIH treatment induced lipid droplets (LDs) accumulation in hippocampal nerve and glia cells of C57BL/6 mice, and caused severe neuro damage including neuron lesions, neuroblast (NB) apoptosis and abnormal glial activation. Studies have shown that the neuronal metabolism disorders might contribute to the CIH induced-hippocampal impairment. Mechanistically, the results showed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In health conditions, neurons do not present high lipid droplet contents since they have a lower capacity to use lipids for energy production [52]. However, lipid droplets are increased in neurons in several neurodegenerative diseases [53][54][55][56], and it is associated with cognitive impairment [57].…”
Section: Discussionmentioning
confidence: 99%
“…In health conditions, neurons do not present high lipid droplet contents since they have a lower capacity to use lipids for energy production [52]. However, lipid droplets are increased in neurons in several neurodegenerative diseases [53][54][55][56], and it is associated with cognitive impairment [57].…”
Section: Discussionmentioning
confidence: 99%
“…38 Chronic hypoxia in SAS leads to the production of a large amount of reactive oxygen species (ROS), activating the JNK/SREBP/ACC pathway in neurons and glial cells, ACC catalyzes the carboxylation of acetyl-CoA to malonyl-CoA, thereby leading to an increase in fatty acid synthesis and abnormal accumulation. 39 In OA, changes in lipid metabolism may be a cause of the disease, studies have observed lipid deposition in joints before histological changes occur, proteomic analysis has revealed significant connections between OA and lipid metabolism, with adipokines identified as key regulatory factors in the pathogenesis of OA. 40 In-depth future research into TNF, IL-17, and lipid metabolism pathways could offer a valuable theoretical foundation for treating the comorbidity of OA and SAS.…”
mentioning
confidence: 99%